Effect of inflation adjustments on inventories - Gül, Meltem (My University, 2024)
This study examines the effect of inflation accounting, which has been brought to the agenda again due to the increasing inflation in recent periods, on inventories, which is one of the non-monetary items. The case study method was used. Based on the Borsa Istanbul sector index, the inventories item in the financial statements of 6 enterprises operating in the Forestry Products and Furniture sector was subjected to inflation adjustment with the simple average method according to the producer price index 2022. As a result of the inflation adjustment, it was observed that the inventory item increased, and the same increase caused an increase in the equity item.
Keywords: İşletme